Seasonal and Spatial Detection of Pesticide Residues Under Various Weather Conditions of Agricultural Areas of the Kilombero Valley Ramsar Site, Tanzania - Materu, Silvia F.; Heise, Susanne; Urban, Brigitte (Frontiers in Environmental Science, 2021)
This study was conducted in the Kilombero Valley Ramsar Site (KVRS), the largest low-altitude freshwater wetland in East Africa to: 1) determine pesticide contamination of soil, water, and sediment at different seasonal weather conditions 2) critically analyze the seasonal and spatial ecological impacts of pesticide contaminations under tropical weather conditions 3) estimate the potential environmental risks from pesticide exposure based on analytical data. Surface sediments, soil and water samples were collected from sugarcane, teak and rice plantations of the KVRS during the dry (January 2012) and the rainy (March–April 2013) seasons. Samples were screened for 97 different types of pesticide residues using and LC–MS and HPLC–MS. Physical-chemical properties of the sediment and soil samples and meteorological data were analyzed. 92% of soil and sediment samples had relatively low OM content (<5%) while 60% of samples had high clay content, indicating high cation exchange capacity that can bind pesticides to the soils. Field soil and air temperature ranging 28–35°C, total sunshine hours-208 h/month, photo radiation −764 MJ/m2, average precipitation 300 mm/month, wind speed >60 km/h, humidity >80% were recorded. Frequency of detection and concentration of pesticides residues depended on seasons. For the dry season sampling, glyphosate/AMPA (0.01–0.55 µg/g), and diuron (0.026–1.7 µg/g) were mostly detected in the sediment and soils. Monuron (1.28–3.9 µg/L) and propoxur (0.05–0.6 µg/L) were mostly detected in the rainy seasons (water and sediments). Glyphosate was above limit of detection in the dry season water samples indicating that its emission into the water system may have been directly through application. Maximum diuron concentrations in water were >30 times higher than the estimated predicted no-effect concentration (PNEC) value (0.054 µg/L) indicating a risk to aquatic community. Calculated pore water concentrations (0.992–0.081 µg/L), exceeded the estimated PNEC values during the dry season, indicating a risk to benthic organisms. Detection of pesticide is influenced by application, environmental factors and the timing of sampling. Further research is recommended to increase our knowledge on soil-water-sediment interactions in the tropics with regard to pesticides.